Bibliometric Analysis of Higher Order Thinking in 2012-2021 - Nainggolan, Icha Ananda (Tauladan Fathimah Azzahra, 2022)
Currently, we are in a new era, namely the era of digital industrialization. Almost all needs from human are based on digital and internet. Therefore, in a world that is constantly changing, teachers in schools must train student’s HOTS so that they are trained solving problems. The goal of this research to analyze information about HOTS publications, author productivity levels, country, keywords, and citations from higher order thinking skills article in 2012-2021. Data collection is done using Publish of Perish (POP). Researcher use google scholar as a data source. Data from POP then analyzed using VOS Viewer software and other map visualizations that do not appear in VOSviewer were explored and analyzed manually. The results showed that the most productive writer was Retnowati, H with 11 publications, keyword visualization resulted in 8 clusters, the highest publication was in 2019 with a percentage of 22.12%, the most cited articles were articles with the title “Teaching to Test or Testing to Teach : Exams Requiring Higher Order Thinking Skills Encourage Greater Conceptual Understanding” written by JL Jensen, MA McDaniel, SM Woodard was cited 301 times and the country with the highest number of documents was occupied by Indonesia with 694 documents